Accounting shared services and its feasibility for implementation in charities. - Ong, Belicia Meiling. (2011)
Our research paper aims to obtain a deeper understanding of the issues that charities encounter with the accounting regulatory requirements and explore the feasibility of outsourcing accounting function to alleviate the problems identified. Through this research, we hope to be able to contribute by helping regulatory bodies understand the struggles of charities to meet accounting requirements and to cater solutions to help alleviate the problems.